The Post-Colonial Concept of Hybridity and Cultural Identity in Rushdie’s Satanic Verses (Eurasian Journal of Humanities and Social Sciences, 2022)
The Satanic Verses is considered the most controversial and stirring novel ever written by Rushdie. It captured the fundamental aspects of the lives of migrants in foreign countries, especially in Western nations like England. Rushdie illustrates that “If the Satanic Verses is anything, it is a migrant's-eye view of the world”